Innovative forms of rehabilitation: Enhancing communities of practice through the art of drumming. Issue 5 (20th October 2019) - Hill, John C.; Hains, Kristina D.; Hains, Bryan J.
ABSTRACT: Communities of place, practice, and interest have historically been impacted by mind and mood-altering substances for quite some time. The development and strength of informal social bonds are important in determining an individual's behavior, and can explain changes in criminal behavior over time. This can impact the social fabric of community, as well as creating the possibility of a community of practice (COP) for rehabilitation. Blending the concepts of emotional intelligence, drumming, and community development, this study examines a community of practice in which individuals with a history of drug use engage in a collective learning process utilizing drumming as the context. The purpose was to explore how a community of practice could be developed through a rehabilitation group program. Results indicated themes of solidarity, development of agency, enhanced communication skills, and the meaning of community being particularly salient throughout the intervention. Future directions for research and practical applications are also presented.